THE PROBLEMAZATION IN THE FREIRE’S PERSPECTIVE AND IN PROBLEM-BASED LEARNING: APPROACHES AND DISTINCTIONS - Pacheco, Lucas Carvalho (2024)
In contrast to traditional education, there are various problematizing perspectives in Education, including the perspective of Brazilian educator Paulo Freire and Problem-Based Learning (PBL). In this sense, this study is guided by the following research problem: what are the approaches and distinctions in the conception of problematization between the Freirean and PBL perspectives? To address the proposed problem, the conception of problematization for each of the references was characterized, based on qualitative research in the basic literature of the Freirean perspective and in theses and dissertations for the PBL perspective. After this characterization, approaches and distinctions in the conception of problematization in both perspectives were identified. Among the approaches, we highlight: both start from a problem situation, depend on dialogue, and have interdisciplinary potential. Regarding the distinctions, we emphasize: the relationship between educator and learner is not hierarchical for Freire, whereas in PBL the learner is the protagonist; furthermore, the Freirean perspective is grounded in the concrete reality of the learners, while PBL is based on experiential learning.